Physiological effects and reduced tolerance following maternal metal exposure in the live‐bearing fish Gambusia affinis. (June 2015) - Cazan, Alfy Morales; Klerks, Paul L.
Abstract The present study assessed the effects of maternal copper or cadmium exposure in a live‐bearing fish. After a 10‐d exposure to background levels (control) or 0.15 μM copper or cadmium, gravid females were transferred to clean water. Once a female gave birth, the authors analyzed her newborn offspring for lipid peroxidation, elemental composition (copper, cadmium, and calcium), and metal tolerance. The authors raised other offspring until sexual maturity and analyzed their growth rate, incidence of abnormalities, and sex ratio. Their earlier research, using the same species and exposure design, demonstrated that cadmium and copper were transferred from gravid females to their offspring. The present study showed that offspring of copper‐exposed females had a reduced size at birth, developmental abnormalities, elevated tissue cadmium levels, and reduced tissue calcium levels. Offspring of cadmium‐exposed females had elevated levels of lipid peroxidation, developmental abnormalities, and lower tissue levels of both copper and calcium. No effects were detected with respect to offsprings' growth rate or sex ratio. Offspring of metal‐exposed fish had a reduced tolerance to the metal that their female parent had been exposed to, and the tolerance showed an inverse relationship to the tissue metal level in the offspring. The latter indicates that the reduced tolerance was the result of an increased body burden prior to the tolerance quantification. The present study constitutes the first report in live‐bearing fishes showing that maternal metal exposure has a wide range of negative impacts on the offspring. Environ Toxicol Chem 2015;34:1337–1344. © 2015 SETAC